2022
DOI: 10.1155/2022/8027712
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic correlates of Adequate Maternal Care in Bangladesh: Analysis of the Bangladesh Demographic and Health Survey 2017-18

Abstract: Introduction. In recent times, Bangladesh has made significant improvements in various health outcomes, but not so much in maternal death. The current flat trend in reducing maternal mortality in Bangladesh has been mainly due to the lower coverage of maternal health care. To improve the coverage, it is essential to find biosocial factors related to adequate maternal health care. Therefore, this study is aimed at finding out the socioeconomic correlates of adequate maternal health care in Bangladesh. Methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(36 reference statements)
1
2
0
Order By: Relevance
“…Household wealth status is a significant factor in determining maternal health care. As per the findings of this study, mothers with poor socioeconomic status face a greater risk of being underweight than those with high socioeconomic status, which is consistent with a previous study [50]. This research aligns with previous studies that have linked wealth index and working women to maternal underweight and overweight/obesity [51].…”
Section: Plos Onesupporting
confidence: 92%
“…Household wealth status is a significant factor in determining maternal health care. As per the findings of this study, mothers with poor socioeconomic status face a greater risk of being underweight than those with high socioeconomic status, which is consistent with a previous study [50]. This research aligns with previous studies that have linked wealth index and working women to maternal underweight and overweight/obesity [51].…”
Section: Plos Onesupporting
confidence: 92%
“…Personal, family or community characteristics that one cannot directly influence are acknowledged as circumstances 18. Studies have demonstrated that utilisation of maternal healthcare opportunities is affected by different factors such as wealth status, living area and educational levels 19–21. Mothers can have considerably limited influences on these distinctive grouping factors.…”
Section: Methodsmentioning
confidence: 99%
“…18 Studies have demonstrated that utilisation of maternal healthcare opportunities is affected by different factors such as wealth status, living area and educational levels. [19][20][21] Mothers can have considerably limited influences on these distinctive grouping factors. Therefore, in the context of this study, these stratified characteristics can be classified as circumstances.…”
Section: Circumstancesmentioning
confidence: 99%